The Cushing Reflex: Oliguria as a Reflection of an Elevated Intracranial Pressure - K. Leyssens; T. Mortelmans; T. Menovsky; D. Abramowicz; Marcel Th. B. Twickler; L. Van Gaal (Case Reports in Nephrology)
Oliguria is one of the clinical hallmarks of renal failure. The broad differential diagnosis is well known, but a rare cause of oliguria is intracranial hypertension (ICH). The actual knowledge to explain this relationship is scarce. Almost all literature is about animals where authors describe the Cushing reflex in response to ICH. We hypothesize that the Cushing reflex is translated towards the sympathetic nervous system and renin-angiotensin-aldosterone system with a subsequent reduction in medullary blood flow and oliguria. Recently, we were confronted with a patient who had complicated pituitary surgery and displayed multiple times an oliguria while he developed ICH.